A complexa produção da intersetorialidade no campo da saúde mental - Carvalho, Rafael Nicolau (2015)
The debate on the intersectoral emerges from the recognition that no public policy is able to unilaterally respond to the complex demands that arise in the social sphere. These demands have historically been answered through focused and fragmented actions by state with sectorial public policies. Intersectoriality is addressed by different fields and areas of knowledge that approach it both as a management model, from an instrumental perspective, as a professional practice model. In the health area is conceived as articulation of different sectors to the achievement of promotion, prevention and recovery of health being aggregated to the principle of integrity. The intersectorality in this area has also coated as a professional strategy for the effectiveness of health care. Therefore, this thesis discusses the intersectionality from their inclusion in the field of mental health by the evidence that the discussion on the theme has become dense in this field and has contributed to the structuring of the Brazilian mental health policy and new care practices. This thesis aims to understand the construction and materiality of intersectionality in the mental health field as well as the professional practices of care under this policy. The motivation to investigate this theme arises from the experiences of the researcher in the field of health and projects developed in the context of mental health. The research consists of a qualitative study which elects the comprehensive perspective as the way to interpret social actions. It was defined the method of triangulation as a research strategy when using the systematic bibliographic search and field research with health network professionals from the municipality of João Pessoa, Paraíba, Brazil. A literature review was conducted based on a research of scientific articles in the SciELO database with the following keywords: intersectorality; mental health and psychiatric reform; mental health and intersectorality. It was selected 239 articles published between 2001 and 2014. The documental research considered all the documents relating to mental health edited in the same period. For field research we used the following techniques: focus group, semi-structured interview and sociodemographic questionnaire. The data collection took place in Psychosocial Care Centers (CAPS), in the form III, Childhood CAPS, CAPS Alcohol and Drugs and Emergency Care in Mental Health (PASM), substitute services that integrate mental health network of the municipality. The empirical data was collected from 04 focus groups, one for each service; 14 interviews and 30 questionnaires applied to the toplevel health professionals. Data collection went from January to July 2014. The research enabled the construction of an interpretive model to approach the intersectorality in its various dimensions, which was used for reading the empirical data. The results suggest that professionals construct several arrangements to give materiality to intersectoral action. From the results it was possible to produce a typology which brings together the main practices identified among professionals who work in the mental health network.